Use of Independent System Animal Feed Lawn Mowing Machine at Sunan Gunungjati Ba'alawi Islamic Boarding School, Gunungpati Semarang - Subekti, Niken; Maulana, Sonika; Rifa’atunnisa, Rifa’atunnisa; Juhadi, Juhadi; Rozi, Fahrur; Setyanto, Heru (Universitas Negeri Semarang, 2024)
Farmer awareness in Cottage Sunan Gunung Jati Islamic Boarding School Ba'alawi Gunungpati Semarang city for improve quality and income in the group breeder . There are breeders in that environment just make feed cattle in a way traditional without use machine , then create a livestock group to be able to process it quality feed . The technological transformation developed is improve feed quality cattle using manufacturing technology machine enumerator grass . Machine manufacturing technology enumerator grass feed cattle For increase income, How breeder get tool cutter grass in accordance with need feed and energy efficiency . Machine manufacturing enumerator grass is a new innovative technology for downstreaming products resulting from the UNNES team's research. Service Team This much needed to support energy efficiency and upgrades coffee quality . Machine manufacturing technology enumerator grass , able to increase income breeders , improve feed quality and energy efficiency . Machine manufacturing enumerator grass is a new innovative technology for downstreaming products resulting from research by the Community Service team UNNES. During the activity, mentoring and monitoring and evaluation were carried out to measure target achievement.